Stabilizing and Anti-Repressor Elements Effectively Increases Transgene Expression in Transfected CHO Cells - Li, Qin; Yan, Rui-Fang; Yang, Yong-Xiao; Mi, Chun-liu; Jia, Yan-long; Wang, Tian-Yun (Frontiers in Bioengineering and Biotechnology, 2022)
Chinese hamster ovary (CHO) cells are currently the most widely used host cells for recombinant therapeutic proteins (RTPs) production, the yields of RTPs need to be increased further. Stabilizing and anti-repressor elements (STAR) can enhance transgene expression levels, but the effect of STAR on RTPs production in CHO cells remains unclear. In this study, we selected three STARs from the human genome, including the human STAR7, STAR40 and STAR44 elements, they were cloned upstream of the promoter element in the eukaryotic vector, followed by transfection into CHO cells, then screened using G418 pressure. Flow cytometry was used to detect enhanced green fluorescent protein (eGFP) expression levels. The gene copy numbers and mRNA expression levels were detected by quantitative real-time PCR. Furthermore, Adalimumab was used to test the selected more strong STAR element. The results showed that eGFP expression levels in the STAR-containing vectors were higher than that of the control vector, among which STAR7 and STAR40 significantly increased eGFP copy numbers and its mRNA expression levels as compared with the control vector. Also, the STAR40 enhanced higher level of Adalimumab expression than STAR7 in transfected CHO cell. Taken together, STARs can enhance the transgenic expression in stably transfected CHO cells, and STAR7 can significantly enhance eGFP gene expression level, but STAR40 increased Adalimumab expression level was higher and more stabilized than that of STAR7 during the long-time culture.